WORKSHOP PENGOLAHAN LIMBAH KULIT BAWANG MERAH MENJADI SABUN CUCI PIRING RAMAH LINGKUNGAN DI DESA PEJANGKUNGAN KECAMATAN PRAMBON KABUPATEN SIDAORJO, JAWA TIMUR - Iif Hanifa Nurrosyidah; Danang Afi Kurniawan; Dedi Murdiyanto (Jurnal Bakti untuk Negeri, 2023)
Onion skin waste is one of the problems in Pejangkungan Village, Prambon District, Sidoarjo Regency. Therefore, we carry out community service activities with the aim of providing education and skills to the Pejangkungan Village Community, especially the PKK women's group, to process onion skin waste into environmentally friendly dish soap. The method implemented in this activity is through an outreach program about the benefits of shallot skins and workshops for the Pejangkungan Village PKK group regarding the processing of shallot skin waste into environmentally friendly dish soap. The conclusion of this activity is being able to provide information to the public regarding the processing of shallot skin waste into environmentally friendly dish soap from ingredients that are easily available and can be used immediately.